2019
DOI: 10.1038/s41598-019-45518-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular alterations in rats with Parkinsonism induced by 6-OHDA and treated with Domperidone

Abstract: After Alzheimer, Parkinson disease (PD) is the most frequently occurring progressive, degenerative neurological disease. It affects both sympathetic and parasympathetic nervous systems in a variable fashion. Cardiovascular symptoms are present in almost all stages of PD and narrower heart rate variability is the earliest sign. Administration of Levodopa to PD patients has proven to provide some degree of neurological protection. This drug, however, causes side effects including nausea and vomiting, lessened by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
19
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 51 publications
5
19
2
1
Order By: Relevance
“…However, none of the currently available animal models can completely reproduce the clinical characteristics of PD (21), although the unilateral 6-OHDA model used in the present study remains the most widely used model for experimental studies of PD in rats (22,23). Importantly, the immunohistochemical and cardiovascular data demonstrated here are consistent with previous studies of Parkinsonism in the unilateral 6-OHDA animal model of PD, suggesting that the rats were adequately lesioned (7,8,10,19,22).…”
supporting
confidence: 85%
See 3 more Smart Citations
“…However, none of the currently available animal models can completely reproduce the clinical characteristics of PD (21), although the unilateral 6-OHDA model used in the present study remains the most widely used model for experimental studies of PD in rats (22,23). Importantly, the immunohistochemical and cardiovascular data demonstrated here are consistent with previous studies of Parkinsonism in the unilateral 6-OHDA animal model of PD, suggesting that the rats were adequately lesioned (7,8,10,19,22).…”
supporting
confidence: 85%
“…These studies demonstrated that several ECG parameters reflect autonomic dysfunction or disease progression, strongly suggesting that clinicians should pay more attention to ECG abnormalities when treating patients with PD (3,(12)(13)(14). From an experimental point of view, several authors have also described cardiovascular changes in PD animals, which could be directly linked to cases of sudden death (7)(8)(9)(10). Thus, a recent study conducted by our research group showed that animals subjected to 6-OHDA showed a reduction in HR and greater variability of heartbeats using the Poincaré plot technique (10), which allows us to gain new insights into the dynamics of cardiac neural mechanisms (15).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to impaired voluntary movements, 6-OHDA-injured rats exhibit a variety of nonmotor disturbances [ 17 ]. Some studies have shown that 6-OHDA-treated rats have lower patterns of HR and HRV than their control counterparts [ 18 , 19 , 20 ]. Knowledge of the pathological dysfunctions in an animal model is critical for recognizing prospective therapeutic targets as adjunctive therapies aimed at multiple levels of pathology are required in PD.…”
Section: Introductionmentioning
confidence: 99%